Systematic review of the effectiveness of health promotion interventions targeting obesity prevention in school-based staff. (5th July 2022) - Hill, Amy; Alston, Laura; Needham, Cindy; Peeters, Anna; LaMontagne, Anthony D; Nichols, Melanie
Abstract: School-based employee interventions can benefit the health of staff and have the potential to influence the health of school students through role-modelling. However, interventions within schools typically focus on students, with very few studies addressing obesity and related health behaviours among school staff. A systematic review of the peer-reviewed literature published between January 2000 and May 2020 was undertaken to synthesize the evidence on the impact that school-based obesity prevention programmes have on the staff they employ. Search terms were derived from four major topics: (i) school; (ii) staff; (iii) health promotion and (iv) obesity. Terms were adapted for six databases and three independent researchers screened results. Studies were included if they reported on the outcomes of body weight, dietary behaviours and/or physical activity. Of 3483 papers identified in the search, 13 studies met the inclusion criteria. All 13 studies included an intervention that focussed on improving nutrition, physical activity or both. All included studies demonstrated a positive outcome for either dietary intake, weight or body mass index or physical activity outcomes, however not all results were statistically significant. The included studies showed promising, although limited, impacts on employee health outcomes. This review demonstrated a lack of global focus and investment in interventions targeting school staff, particularly in contrast to the large amount of research on school-based health promotion initiatives focussed on students. There is a need for further research to understand effective interventions to promote health and prevent obesity in this large, diverse and influential workforce. Lay Summary: School-based health promotion interventions that focus on employees can benefit the health of staff and have the potential to also influence the health of school students through role-modelling. Most published intervention studies within schools have typically focussed on students, however, with very few studies addressing obesity and related health behaviours among school staff. This systematic review summarizes the evidence on the impact of school-based obesity prevention programmes on the outcomes of physical activity, weight or dietary practices of school staff. The search identified 13 relevant studies published since 2000. The findings of this review show that school staff focussed health promotion interventions can positively impact obesity-related outcomes. The small number of available studies, however, demonstrates a lack of research focus and investment in interventions targeting school staff and teachers' health. The majority of included studies used relatively weak study designs and included small numbers of schools and staff members. This is particularly contrasting to the large body of research on school-based health promotion initiatives focussed on students. There is a need for further research to understand effective interventions to promote health and prevent obesity in this large, diverse and influential workforce.